Determinants of Policy Failure in Mataram Metro and Its Implications for the Sustainability of Trans Mataram - Daffa Pratama; Muhamad Safriansyah; Baiq Imaniar Cahyani; Siti Atika Rahmi; Muhammad Aprian Jailani; Ayatullah Hadi (Master of Public Administration FISIPOL Universitas Negeri Surabaya, 2026)
The rapid urban expansion of Mataram City as a National Activity Center has intensified transportation challenges, particularly traffic congestion caused by high dependence on private vehicles and the limited effectiveness of public transportation services. This study aims to analyze the determinants of policy failure in the implementation of the Mataram Metro Bus program and to examine the strategic adaptation measures introduced through the Trans Mataram 2026 initiative. The research employs a descriptive qualitative approach, with data collected through in-depth interviews, field observations, and document analysis. The analytical framework is based on William N. Dunn’s policy evaluation theory, focusing on effectiveness, responsiveness, and policy sustainability. The findings reveal that the failure of the Mataram Metro Bus was primarily driven by the incompatibility between large bus dimensions and existing urban road infrastructure, irregular waiting times that reduced service reliability, and the absence of comprehensive supporting regulations and institutional coordination. In response, the Trans Mataram 2026 program introduced adaptive reforms, including the deployment of smaller and more flexible fleets, the integration of real-time digital tracking systems to improve service responsiveness, and the implementation of a zero-fare policy for vulnerable groups to enhance accessibility and social inclusion. The study concludes that the sustainability of urban mass transit systems in medium-sized cities depends significantly on contextual policy design, technological integration, and user-centered service innovation. These findings contribute to the development of more adaptive and inclusive public transportation policy models.